Circadian modulation of sodium-potassium ATPase and sodium - proton exchanger in human erythrocytes: in vitro effect of melatonin - Chakravarty, S.; Rizvi, S. I. (Cellular and Molecular Biology, 2011)
Melatonin (N-acetyl-5-methoxytrptamine) is a pineal secretory product which is involved in the regulation of circadian rhythm and participates in many physiological functions. It also acts as a potent antioxidant and a powerful free radical scavenger. The membrane-associated Na+/K+-ATPase and Na+/H+ exchanger in erythrocytes play an important role in maintaining cytosolic pH, ionic homeostasis, cell osmolarity and in the regulation of transmembrane ion movement. The present work was undertaken to determine the role of melatonin in modulating the activity of Na+/K+-ATPase and Na+/H+ exchanger in human erythrocytes. Our observation shows circadian modulation of Na+/K+-ATPase and Na+/H+ exchanger which may have important therapeutic implications. Exogenous melatonin modulated the activities of Na+/K+-ATPase and Na+/H+ exchanger in human red blood cells, this effect may in part be explained due to the antioxidative effect of melatonin and also due to modulation of membrane fluidity. Further work is needed to understand the mechanism of action.